Caffeine supplementation as an ergogenic aid for muscular strength and endurance: A recommendation for coaches and athletes - Brooks, J. H.; Wyld, K.; Chrismas, B. C. R. (Journal of Athletic Enhancement, 2016)
Caffeine (1, 3, 7-trimethylxanthine) which can be ubiquitously found in energy drinks, sodas, coffee, and supplements, is one of the principal legal drugs consumed worldwide. Caffeine based ergogenic aids are utilized prolifically within training and competition for an ergogenic benefit to enhance sporting performance by both recreational and elite athletes. The evidence of caffeine's ability to enhance endurance performance is well established, however, evidence of an ergogenic benefit for muscular endurance and strength-based tasks is limited. Moreover, the limited evidence for caffeine`s ergogenic benefit in muscular endurance and strength is equivocal, and therefore,practical recommendations for the implementation of caffeine supplementation in training and competition for coaches, and practitioners is difficult. Indeed, it is currently not known if, and how caffeine may improve muscular endurance and/or strength based tasks. Variability in the findings could be due to several factors including muscles tested, participant characteristics, exercise protocol, type and dose of caffeine used. This brief review will discuss the current literature relating to the potential efficacy of caffeine to enhance muscular endurance and strength based performance, and provides evidence based recommendations for athletes and coaches to implement.